2014
DOI: 10.4172/2155-6156.1000369
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Disease Knowledge with Adherence to Drug Therapy, Blood Sugar Levels and Complications Associated with Disease among Type 2 Diabetic Patients

Abstract: Background: Low adherence to medication is a growing concern, seriously undercutting the benefits of current medical care. Present study was plannedon the assumption that knowledge regarding diabetes might be important contributory factor affecting adherence to the treatment regimen, which is crucial in glycemic control &complications related to the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Adherence in patients with type 2 diabetes is generally defined as the level of behavior of someone who is getting treatment for diet, taking medication and carrying out a lifestyle in accordance with the recommendations of health care providers [24] Patients who do not understand DM, often do not comply with DM treatment [25] The success of DM treatment is highly dependent on the patient's compliance with taking medication. Several previous studies on the relationship between knowledge and adherence to taking medication have shown different results [26][27][28] .…”
Section: Discussionmentioning
confidence: 94%
“…Adherence in patients with type 2 diabetes is generally defined as the level of behavior of someone who is getting treatment for diet, taking medication and carrying out a lifestyle in accordance with the recommendations of health care providers [24] Patients who do not understand DM, often do not comply with DM treatment [25] The success of DM treatment is highly dependent on the patient's compliance with taking medication. Several previous studies on the relationship between knowledge and adherence to taking medication have shown different results [26][27][28] .…”
Section: Discussionmentioning
confidence: 94%